Standing Up Against Sexual Harassment in Film: Analyzing Resistance in Penyalin Cahaya (Martabat: Jurnal Perempuan dan Anak, 2023)
The film Penyalin Cahaya, which was released in 2021, garnered public attention because it tackled the issue of sexual harassment in educational institutions. Roland Barthes' semiotic analysis delves deeply into the iconic signs that depict various elements in the film. The research approach used in this study is qualitative, employing a descriptive method. The results show that the film Penyalin Cahaya portrays several signs related to cases of sexual harassment, affecting not only women but also men. Additionally, the film depicts the settlement of sexual harassment cases, where the perpetrators are often those who hold power and can describe the dominant ideological factors that still exist in society. In this film, the perpetrators of sexual harassment abuse their power and their parents' wealth to cover up their crimes and silence their victims. Consequently, the victims must fight against the unjust systems in place and seek justice for the sexual harassment they endured